2022
DOI: 10.1088/1748-9326/aca16a
|View full text |Cite
|
Sign up to set email alerts
|

Ambient fine particulate matter and ozone pollution in China: synergy in anthropogenic emissions and atmospheric processes

Abstract: Since 2013, China has taken a series of actions to relieve serious PM2.5 pollution. As a result, the annual PM2.5 concentration decreased by more than 50% from 2013 to 2021. However, ozone pollution has become more pronounced, especially in the North China Plain. Here, we review the impacts of anthropogenic emissions, meteorology, and atmospheric processes on ambient PM2.5 loading and components and O3 pollution in China. The reported influence of interannual meteorological changes on PM2.5 and O3 pollution du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 169 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…The NO x emission affects the OA concentration by changing the HO x (OH + HO 2 ) and ozone concentration, which determines the conversion rates of OA precursors. Most of the urban cities are in VOC-limited and transitional regimes, 46,47 and the reduction of NO x would elevate the oxidation capacity and worsen the OA pollution. From 2005 to 2014, the NO x emission increased markedly and lowered the HO x level, hence resulting in lower SOA concentration (−0.2 μg/m 3 ), which is quite the opposite case from the period of 2014−2019, when Figure 6 and Table S6 show the influence of NO x concentration on OH, HO 2 , O 3 , and SOA concentrations in three metropolitans, i.e., Beijing, Shanghai, and Guangzhou.…”
Section: Policy Implications For Oa Control In Key Regions In Chinamentioning
confidence: 99%
“…The NO x emission affects the OA concentration by changing the HO x (OH + HO 2 ) and ozone concentration, which determines the conversion rates of OA precursors. Most of the urban cities are in VOC-limited and transitional regimes, 46,47 and the reduction of NO x would elevate the oxidation capacity and worsen the OA pollution. From 2005 to 2014, the NO x emission increased markedly and lowered the HO x level, hence resulting in lower SOA concentration (−0.2 μg/m 3 ), which is quite the opposite case from the period of 2014−2019, when Figure 6 and Table S6 show the influence of NO x concentration on OH, HO 2 , O 3 , and SOA concentrations in three metropolitans, i.e., Beijing, Shanghai, and Guangzhou.…”
Section: Policy Implications For Oa Control In Key Regions In Chinamentioning
confidence: 99%
“…Recently, stringent laws have been established to regulate atmospheric pollution, which has caused a considerable shift in the emission patterns of anthropogenic pollutants. For example, emissions of SO 2 and NO x in China have been considerably reduced, whereas NH 3 emissions have remained stable and O 3 concentrations have increased . Although SO 2 considerably enhanced aerosol particle formation at low NH 3 levels and some studies have shown that an increase in NH 3 concentration may increase SOA formation through the formation of ammonium nitrate, , this study found that an increase in NH 3 concentration may weaken the enhancement effect of SO 2 on biogenic SOA formation.…”
Section: Resultsmentioning
confidence: 51%
“…For example, emissions of SO 2 and NO x in China have been considerably reduced, whereas NH 3 emissions have remained stable and O 3 concentrations have increased. 52 Although SO 2 considerably enhanced aerosol particle formation at low NH 3 levels and some studies have shown that an increase in NH 3 concentration may increase SOA formation through the formation of ammonium nitrate, 53,54 this study found that an increase in NH 3 concentration may weaken the enhancement effect of SO 2 on biogenic SOA formation. Thus, while analyzing the impacts of NO x , SO 2 , and NH 3 on the production of SOA, their concentration levels should be carefully considered.…”
Section: General Molecular Characteristicsmentioning
confidence: 57%
“…Liu et al found that meteorological conditions change in 2050 under RCP8.5 would increase PM 2.5 concentration in most regions in eastern China when anthropogenic emissions are held constant as in 2015, but decrease PM 2.5 concentrations when anthropogenic emissions are reduced largely. Even if large uncertainties in studies on climate change due to different model configurations and scenario settings, large emission reduction is expected to release additional challenges by climate change. Furthermore, we need to point out that climate change and meteorological conditions have an impact on nature emissions and pollution transport patterns. , Thus, the response of China to transboundary pollution and background concentration would change in the future.…”
Section: Resultsmentioning
confidence: 99%